FORMULASI TABLET HISAP EKSTRAK KUNYIT (Curcuma domestica) DENGAN KOMBINASI BAHAN PENGISIMANITOL – AMILUM MANIHOT - Farida Haryanti; Indah Purwantini; T. Nanda Saifullah Sulaiman (Majalah Obat Tradisional, 2012)
Hydroalcoholic extract of turmeric is recommended as supplement to prevent atherosclerosis, but the common dosage form in traditional practices is less practical and unacceptable. It is therefore recommended to be mad into new dosage form, lozenges. This research aims to determine the effect of filler agent manitol-amylum manihot variations to the physical characteristics of granule, tablet, and the flavor of the tablet. The optimum formula was evaluated with simplex lattice design method. The hydro extract of turmeric was made using aquadest 80OC while the alcoholic extract using ethanol 96%. Hydro alcoholic extract was made by mixing both extracts, wet granulated and formulated into five formulas with combination of manitol-amylum manihot ratio. The result showed that the combination of manitol-amylum manihot had affected the tablet hardness, solubility time and flavor acceptance. The formula with the combination manitol-amylum manihot 80% : 20% was found to be the optimum formula.